Modes of modality : modality, typology, and universal grammar - Leiss, Elisabeth; Abraham, Werner (Studies in language companion series, 2014)
Modality is one of the grammatical categories in Igbo language studies that received the least attention within the last century. There is, however, a growing awareness that the category of modality is expressed in the language through specific verbs and suffixes that have recently been (re- )categorised as modal verbs and modal suffixes, respectively (Uchechukwu 2008, 2011). This paper explores further the issue of modality in Igbo by focusing on the constructions and lexical items that could be involved in the implicit expression of modality in the language. The different types of constructio.